1990
DOI: 10.1300/j010v14n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Not Receiving Adequate Prenatal Care in an Urban Black Population

Abstract: REcords of 36,608 Black single live births and 762 infant deaths in Washington, D.C., from 1980 to 1985 were analyzed. Bivariate and multivariate contingency table analysis were carried out to identify the groups at high risk for not obtaining adequate prenatal care. Results show that the groups of mothers which are less likely to receive adequate care also have a high risk of delivering low birthweight infants even when they receive adequate care. The paper focuses on women with high gravidity and short birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In studies from Jamaica (McCaw Binns et al . 1995) and USA (Ahmed et al . 1990) it was also found that an adverse pregnancy outcome was associated with more antenatal visits in the following pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In studies from Jamaica (McCaw Binns et al . 1995) and USA (Ahmed et al . 1990) it was also found that an adverse pregnancy outcome was associated with more antenatal visits in the following pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The disparity is even greater in D.C. (67.1% and 90.9% respectively in 1999) [12]. Minority women from poor urban communities, such as D. C., enter prenatal care later and have fewer prenatal care visits than white women of higher socio-economic levels [13,14]. Women who make little or no use of prenatal care often are disenfranchised members of the community, such as homeless and substance abusing women [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Even within a well-defined population group, individuals may represent a culturally heterogeneous population [77,89,131,159,160,167,[171][172][173][174][175][176][177]179,184,[187][188][189][190]195].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in medical care delivery [157][158][159][160][161][162][163][164][165][166][167][168][169][170] and health outcomes [171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] have been reported across race, gender, and socioeconomic status. Yet similar differences have also been documented within these seemingly homogeneous ethnic or racial groups .…”
Section: Culture and Health Behaviormentioning
confidence: 99%